Global, Regional, and National Burden of chronic kidney disease in older adults from 1990 to 2021: Results from the Global Burden of Disease Study 2021 - Weixuan Wang; Junhui Wu; Shaomei Shang (PLoS ONE, 2026)
Background Drawing on data from the Global Burden of Disease (GBD) 2021 study, this research provides the first systematic assessment of the burden and trends of chronic kidney disease (CKD) among the global population aged 75 years and over between 1990 and 2021. Unlike previous studies covering the entire age spectrum, this study focuses on the age group with the highest concentration of disease burden and the greatest health vulnerability, with the aim of revealing the unique epidemiological patterns specific to this population. Methods The study methodology involved extracting data on the prevalence, incidence, mortality and disability-adjusted life years (DALYs) for chronic kidney disease (CKD) among people aged 75 years and over in 204 countries and territories from the GBD 2021 database. All reported rates are age-standardized. We calculated estimated annual percentage changes (EAPCs) to analyze trends and examined the association between the disease burden and the Sociodemographic Index (SDI). Results The study found that in 2021, approximately 127 million people aged 75 years and over worldwide were living with CKD. Between 1990 and 2021, the age-standardized prevalence declined slightly (EAPC = −0.06%; 95% UI: −0.09% – −0.03%), whilst incidence, mortality and DALY rates all rose significantly (EAPCs of 0.50%; 95% UI: 0.47%–0.53%, 1.55%; 95% UI: 1.48%–1.61% and 1.07%; 95% UI: 1.02%–1.12%, respectively), demonstrating the key phenomenon of ‘prevalence–mortality trend divergence’. The relationship between the burden of disease and socio-economic development is complex: regions with low SDI bear the heaviest burden of mortality, whilst regions with high SDI have experienced the fastest growth in mortality rates. The study also revealed significant heterogeneity in the burden across age, gender and geographical regions. Conclusions The burden of chronic kidney disease (CKD) among the global older adult population is rapidly shifting from a pattern of ‘high prevalence’ to one characterised by ‘high incidence, high mortality and high disability’, with the underlying drivers exhibiting fundamental differences across regions at various stages of development. This necessitates that public health strategies move beyond a ‘one-size-fits-all’ approach and instead develop highly age-specific and contextually tailored interventions. This study provides a detailed map for understanding the epidemiology of CKD in the context of extreme population ageing, and offers crucial evidence for the allocation of resources and the formulation of policies.